2020
DOI: 10.3847/1538-4357/ab9942
|View full text |Cite
|
Sign up to set email alerts
|

The Streamer Blowout Origin of a Flux Rope and Energetic Particle Event Observed by Parker Solar Probe at 0.5 au

Abstract: The distribution of spacecraft in the inner heliosphere during 2019 March enabled comprehensive observations of an interplanetary coronal mass ejection (ICME) that encountered Parker Solar Probe (PSP) at 0.547 au from the Sun. This ICME originated as a slow (∼311 km s −1 ) streamer blowout (SBO) on the Sun as measured by the white-light coronagraphs on board the Solar TErrestrial RElations Observatory-A and the Solar and Heliospheric Observatory. Despite its low initial speed, the passage of the ICME at PSP wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 102 publications
2
29
0
Order By: Relevance
“…This closed structure observed during the period of bidirectional electrons coincides with the SBO-CME arrival time. During its earlier orbits, PSP encountered SBO-CMEs (Korreck et al 2020;Lario et al 2020;Nieves-Chinchilla et al 2020) and SEP enhancements associated with SBO-CMEs were also observed (Giacalone et al 2020;Lario et al 2020;Mitchell et al 2020a), consistent with our observation.…”
Section: Discussionsupporting
confidence: 91%
“…This closed structure observed during the period of bidirectional electrons coincides with the SBO-CME arrival time. During its earlier orbits, PSP encountered SBO-CMEs (Korreck et al 2020;Lario et al 2020;Nieves-Chinchilla et al 2020) and SEP enhancements associated with SBO-CMEs were also observed (Giacalone et al 2020;Lario et al 2020;Mitchell et al 2020a), consistent with our observation.…”
Section: Discussionsupporting
confidence: 91%
“…G. Richardson, 2014;Riley et al, 2000). Data from the more recently launched Parker Solar Probe, BepiColombo, and Solar Orbiter have resulted in several studies of CMEs measured between the Sun and 1 AU (e.g., E. E. Davies et al, 2021;Korreck et al, 2020;Lario et al, 2020;Nieves-Chinchilla et al, 2020;Zhao et al, 2020;Weiss et al, 2021). Considerable results were also achieved using data from spacecraft, such as Pioneer 10/11 and Voyager 1/2, that were launched on escape trajectories out of the solar system and that have provided valuable information on the behavior of ICMEs at progressively larger heliocentric distances (e.g., Burlaga et al, 2001;C.…”
mentioning
confidence: 99%
“…The encouraging results of the magnetic field hindcast prediction presented in this work suggest that these events could be accurately forecast even if their exact source region remains elusive in on-disc imagery. Certainly, in this and other reported cases off-limb observations were crucial in connecting a stealth CME at the Sun with its interplanetary counterpart (e.g., Korreck et al 2020;Lario et al 2020;O'Kane et al 2021). Thus, this study highlights the importance of continuous observations of the solar disc and corona away from the Sun-Earth line, not only to enable more accurate space weather forecasts, but also to shed light on the complex characteristics and dynamics of stealthy CMEs that, albeit slow, have potential for considerable geoeffectiveness.…”
Section: Discussionmentioning
confidence: 50%